Próby gry z cenzurą w listach z zesłania Kazimierza Szetkiewicza - Szargot, Barbara (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
Tekst dotyczy sposobu w jaki zesłany do Rosji Kazimierz Szetkiewicz pisząc do żony starał się przekonać czytającego te listy cenzora rosyjskiego o tym, że jest lojalnym rosyjskim obywatelem. W tym celu podkreślał swoją niewinność, kłamał, że nie walczył o sprawę niepodległości Polski, wychwalał cara, kulturę rosyjską, nakłaniał żonę do nauki języka rosyjskiego. Dzięki analizie listów Szetkiewicza zyskujemy wiedzę o sposobach jakimi ludzie oszukiwali cenzurę.

The text deals with the way Kazimir Shetkevich, who was exiled to Russia, wrote to his wife and tried to convince the Russian censor reading these letters that he was a loyal Russian citizen. To this end, he emphasized his innocence, lied that he had not fought for the cause of Polish independence, praised the Tsar and Russian culture, and urged his wife to learn Russian. Through the analysis of Shetkevich’s letters, we gain knowledge of the ways in which people cheated the censors.
Attempts at Circumventing Censorship in Kazimierz Szetkiewicz’s Letters from Exile
Keywords: listy; pozytywizm; zesłańcy postycziowi; autocenzura; Letters; Positivism; Post-January Uprising Exiles; Autocensorship